The Importance of Pharmaceutical Dosage Forms in Administration via Enteral Feeding Tubes - Kutay Demirkan; Aygin Bayraktar Ekincioğlu (Galenos Yayinevi, 2016)
SUMMARY A caloric requirement of the patients who do not have an access for feeding through an oral route is supported by enteral or parenteral nutrition. In the patients who have suitable gastrointestinal function, enteral feeding is preferred initially. Enteral feeding is also used for administration of medications in patients who cannot swallow. However, an administration of drugs via a feeding tube is complicated; appropriate techniques should be used in order to prevent obstruction of feeding tube and thereby avoid reduction of the drug effect and to minimize the risk of toxicity of given pharmaceuticals. In the patients who are not able to take medication orally, alternative routes such as intravenous, intramuscular, subcutaneous, inhaled, transdermal, rectal, and sublingual administrations are available and should be preferred at the first place. According to the American Society for Parenteral and Enteral Nutrition, an effect of a size and the position of the feeding tube, characteristics of pharmaceutical dosage form and methods of administration should be considered when applying medication via enteral tube. The risk of the drug interactions arises in patients who have nutritional support. In order to prevent drug interactions, a pharmacist, who has an extensive education and knowledge on drugs, its characteristics and mechanism of action is required for multidisciplinary team in clinical practice.